RETRACTED; Combined rs‐fMRI study on brain functional imaging and mechanism of RAGE‐DAMPs of depression: Evidence from MDD patients to chronic stress‐induced depression models in cynomolgus monkeys and mice. Issue 10 (12th October 2021) - Yan, Weixin; Xie, Lingpeng; Bi, Yanmeng; Zeng, Ting; Zhao, Di; Lai, Yuqi; Gao, Tingting; Sun, Xuegang; Shi, Yafei; Dong, Zhaoyang; Wen, Ge; Gao, Lei; et al.
Abstract: More and more evidence show that major depressive disorder (MDD) is closely related to inflammation caused by chronic stress, which seriously affects human physical and mental health. However, the inflammatory mechanism of depression and its effect on brain function have not been clarified. Based on resting‐state functional magnetic resonance imaging (rs‐fMRI), we investigated change of brain functional imaging and the inflammatory mechanism of damage‐related molecular patterns (DAMPs)—receptor of advanced glycation protein end product (RAGE) in MDD patients and depressive‐like cynomolgus monkeys and mice models induced by chronic stress. The regional homogeneity (ReHo) and functional connectivity (FC) were analyzed using MATLAB and SPM12 software. We detected the expression of DAMPs‐RAGE pathway‐related proteins and mRNA in MDD peripheral blood and in serum and brain tissue of cynomolgus monkeys and mice. Meanwhile, RAGE gene knockout mice, RAGE inhibitor, and overexpression of AVV9 RAGE adeno‐associated virus were used to verify that RAGE is a reliable potential biomarker of depression. The results showed that the ReHo value of prefrontal cortex (PFC) in MDD patients and depressive‐like cynomolgus monkeys was decreased. Then, the PFC was used as a seed point, the FC of ipsilateral and contralateral PFC were weakened in depressive‐like mice. At the same time, qPCR showed that RAGE and HMGB1 mRNA were upregulated and S100β mRNA was downregulated. The expression of RAGE‐related inflammatory protein in PFC of depressive‐like monkeys and mice were consistent with that in peripheral blood of MDD patients. Moreover, the results were confirmed in RAGE –/– mice, injection of FPS‐ZM1, and overexpression of AAV9 RAGE in mice. To sum up, our findings enhance the evidence that chronic stress‐PFC‐RAGE are associated with depression. These results attempt to establish the links between brain functional imaging, and molecular targets among different species will help to reveal the pathophysiological mechanism of depression from multiple perspectives. Abstract : The regional homogeneity value in prefrontal cortex (PFC) of MDD patients and depressive‐like monkeys were decreased and related to the upregulation of RAGE in peripheral or PFC. RAGE is essential for the susceptibility of chronic stress to depression via regulating the functional connectivity of PFC in mice. Overexpression or knockout/inhibition of RAGE in PFC can regulate depressive‐like behavior in mice.